Literasi Media Sosial: Upaya Pencegahan Pemalsuan Identitas Digital - Kurniasih, Nuning (Forum Kerjasama Pendidikan Tinggi, 2023)
The increase in internet usage has led to an increase in cybercrime. One of the crimes in cyberspace is caused by online impersonation. In these conditions, it is important to socialize social media literacy, especially in an effort to prevent digital identity fraud. The purpose of this community service activity is to equip the community with social media literacy in order to avoid the dangers of social media misuse, especially those caused by impersonation or digital identity forgery. The problem was analyzed by reviewing phenomena, news and research findings on social media misuse and crime, especially those related to identity forgery in Indonesia. The training or Webinar material includes an understanding of media literacy, an understanding of social media literacy, knowledge of types of social media misuse, instilling awareness of the dangers of digital identity forgery, knowledge of the types of digital identity impersonation or forgery and efforts to prevent digital identity forgery. The target audiences for this community service activity are students, academics and the general public. The training material was delivered in a Webinar on the Zoom App and broadcast live on the YouTube channel. The understanding of the target audience of the material presented during the community service activity can be seen during the question and answer session or discussion. In this session, it was seen that the target audience asked several questions that were in accordance with the training material presented. From the observations in the Q&A or discussion session, the target audience had a very good understanding of the training material they received.